Fine‐Tuning of Charge‐Conversion Polymer Structure for Efficient Endosomal Escape of siRNA‐Loaded Calcium Phosphate Hybrid Micelles. Issue 13 (8th April 2014) - Maeda, Yoshinori; Pittella, Frederico; Nomoto, Takahiro; Takemoto, Hiroyasu; Nishiyama, Nobuhiro; Miyata, Kanjiro; Kataoka, Kazunori
<x xml:space="preserve">Abstract</x> For efficient delivery of siRNA into the cytoplasm, a smart block copolymer of poly(ethylene glycol) and charge‐conversion polymer (PEG‐CCP) is developed by introducing 2‐propionic‐3‐methylmaleic (PMM) amide as an anionic protective group into side chains of an endosome‐disrupting cationic polyaspartamide derivative. The PMM amide moiety is highly susceptible to acid hydrolysis, generating the parent cationic polyaspartamide derivative at endosomal acidic pH 5.5 more rapidly than a previously synthesized cis‐aconitic (ACO) amide control. The PMM‐based polymer is successfully integrated into a calcium phosphate (CaP) nanoparticle with siRNA, constructing PEGylated hybrid micelles (PMM micelles) having a sub‐100 nm size at extracellular neutral pH 7.4. Ultimately, PMM micelles achieve the significantly higher gene silencing efficiency in cultured cancer cells, compared to ACO control micelles, probably due to the efficient endosomal escape of the PMM micelles. Thus, it is demonstrated that fine‐tuning of acid‐labile structures in CCP improves the delivery performance of siRNA‐loaded nanocarriers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>